Evolution of permeability and Biot coefficient at high mean stresses in high porosity sandstone. (July 2017) - Ingraham, Mathew D.; Bauer, Stephen J.; Issen, Kathleen A.; Dewers, Thomas A.
Abstract: A series of constant mean stress (CMS) and constant shear stress (CSS) tests were performed to investigate the evolution of permeability and Biot coefficient at high mean stresses in a high porosity reservoir analog (Castlegate sandstone). Permeability decreases as expected with increasing mean stress, from about 20 Darcy at the beginning of the tests to between 1.5 and 0.3 Darcy at the end of the tests (mean stresses up to 275 MPa). The application of shear stress causes permeability to drop below that of a hydrostatic test at the same mean stress. Results show a nearly constant rate decrease in the Biot coefficient as the mean stress increases during hydrostatic loading, and as the shear stress increases during CMS loading. CSS tests show a stabilization of the Biot coefficient after the application of shear stress. Highlights: High mean stress evolution of Biot coefficient investigated. Permeability evolves differently under constant mean and constant shear stress. Application of shear stress stabilizes bulk modulus and Biot coefficient.